YTH Domain Proteins: A Family of m6A Readers in Cancer Progression - Xu, Yirong; Zhang, Wei; Shen, Feng; Yang, Xi; Liu, Huilan; Dai, Shengbin; Sun, Xinchen; Huang, Junxing; Guo, Qing (Frontiers in Oncology, 2021)
N6-methyladenosine (m6A) is the most abundant internal modification in eukaryotic messenger RNAs (mRNAs). M6A RNA methylation is involved in all stages of RNA life cycle, from RNA processing, nuclear output, translation regulation to RNA degradation, indicating that m6A has various functions affecting RNA metabolism positively or negatively. Reading proteins are vital in regulating the translation and stability of m6A mRNAs positively or negatively. Recent studies have enhanced the understanding of the molecular mechanism of the YT521-B homology (YTH) domain family and the modification of m6A. This study aimed to review the specific functions, mechanisms, and interactions of the YTH domain protein family. It also discussed future research directions, thus providing new ideas for the clinical diagnosis and targeted therapy of cancer.